Adsorption characteristics of modified wheat husk for the removal of a toxic dye, methylene blue, from aqueous solutions - Banerjee S.; Chattopadhyaya M.C.; Uma; Sharma Y.C. (My University, 2025)
Adsorption characteristics of modified wheat husk for the removal of a toxic cationic dye, methylene blue, from aqueous solutions have been investigated. The adsorbent, wheat husk, was characterized by Fourier transform infrared spectra (FTIR) and scanning electron microscopy (SEM) for its functional group and surface characteristics. The removal decreased by increasing temperature from 303 to 373 K. The removal was found to be pH dependent, and it decreased from 96.2 to 40.7% by varying the pH of the solution from 4.5 to 9.5. It was observed that 93.4% removal of methylene blue was achieved at an initial dye concentration of 13.37 × 10-2 mol/L at 303 K. Equilibrium adsorption data for the removal of methylene blue were analyzed by Langmuir, Freundlich, and Tempkin isotherm models. Values of thermodynamic parameters viz ΔG°, ΔH°, and ΔS° were determined. The negative value of ΔH° confirmed the exothermic nature of removal of methylene blue by adsorption on modified wheat husk. © 2014 American Society of Civil Engineers.